Association between genetic variants in the promoter region of a novel antisense long noncoding RNA RP11‐392P7.6 and colorectal cancer risk. (14th June 2017) - Jin, Mingjuan; Gu, Simeng; Ye, Ding; Li, Yingjun; Jing, Fangyuan; Li, Qilong; Chen, Kun
Abstract : There is a widespread occurrence of antisense transcripts' regulation on cancer‐related genes in cancer biology. RP11‐392P7.6 is antisense to the coding region of cancer‐related gene GPRC5D, which has been found recently. The aim of this study was to investigate the associations of tagSNPs in the promoter region of RP11‐392P7.6 with the risk of colorectal cancer. We conducted a two‐stage case–control study, with a discovery set (320 cases and 319 controls) and a validation set (501 cases and 538 controls). Four tagSNPs (rs1531970, rs1642199, rs4763903, and rs10845671) were selected based on 1000 Genomes Project data and genotyped by using the Sequenom MassARRAY genotyping platform. In the discovery set, three tagSNPs (rs1642199, rs4763903, and rs10845671) were revealed promising associations with the risk of colorectal cancer, among which the rs10845671 variants were further replicated in the validation set (OR = 1.47, 95% CI = 1.10–1.20 in heterozygote codominant model; OR = 1.38, 95% CI = 1.04–1.83 in dominant model). When combined the two sets, the above positive associations remained unchanged. Rs10845671 was found to be associated with an increased risk of colorectal cancer (OR = 1.43, 95% CI = 1.14–1.81 in heterozygote codominant model; OR = 1.35, 95% CI = 1.08–1.69 in dominant model). These findings indicate that rs10845671 may contribute to the susceptibility to colorectal cancer and be a candidate biomarker for colorectal cancer risk prediction. Environ. Mol. Mutagen. 58:434–442, 2017. © 2017 Wiley Periodicals, Inc.